Nav1.8 and Chronic Pain: From Laboratory Animals to Clinical Patients - Yu-Feng Xie (Biomolecules)
As a subtype of voltage-gated sodium channel and predominantly expressed in the sensory neurons located in the dorsal root ganglion (DRG), the Nav1.8 channel encoded by the SCN10A gene is found to have different variants in patients suffering chronic pain or insensitivity to pain due to the gain-of-function or loss-of-function of Nav1.8 channels. In animal models of chronic pain, Nav1.8 is also verified to be involved, suggesting that Nav1.8 may be a potential target for treatment of chronic pain. Another voltage-gated sodium channel, Nav1.7, is also proposed to be a target for chronic pain, supported by clinical findings in patients and laboratory animal models; however, there is no Nav1.7-specific drug that has passed clinical trials, although they demonstrated satisfactory effects in laboratory animals. This discrepancy between clinical and preclinical studies may be related to the differences between humans and laboratory animals or due to the degeneracy in different sodium channels governing the DRG neuronal excitability, which is thought of as the underlying machinery of chronic pain and mostly studied. This review summarizes recent findings of Nav1.8 in chronic pain from clinics and laboratories and discusses the difference, which may be helpful for future investigation of Nav1.8 in chronic pain, considering the dilemma of the Nav1.7 channel in chronic pain.